Robust predictive control of grid-tied converters based on direct power control - Fischer, Jonatan Roberto (2013)
This study focuses on the control of instantaneous complex power of a grid-connected voltage-source inverter (VSI). In this study, a new space-vector-modulation-based direct power control approach is proposed: the robust predictive direct power control (RP-DPC). The proposed predictive control algorithm ensures that both, instantaneous real and imaginary powers, track the reference with high speed and accuracy reducing steady-state errors. In order to reduce the total harmonic distortion (THD) in the output currents, a fundamental frequency positive sequence detector is used in conjunction with a prediction grid voltage observer. Comparative simulations and experimental results of a 10-kW three-phase grid-connected VSI showing the steady-state and transient performance of the proposed RP-DPC are given. A low THD and balanced output currents are maintained even under severe voltage unbalance conditions.